Road Safety Services of a Transport Service Provider: Basis for an Operational Manual - Manangan, Arci V. (International Journal of Scientific Research and Management (IJSRM), 2024)
For all users of the road, road safety is crucial. Everyone is concerned about it because of the dramatic increase in the number of vehicles on the road in recent years, road safety has become even more crucial. According to a 2014 World Health Organization research, motorcycle riders account for more than half of all fatalities in traffic incidents. At 19%, pedestrians make up the second-highest percentage of road user fatalities, after four-wheeled vehicle drivers (14%), and their passengers (11%).   If there are road safety services in place and followed to reduce the high risk of accidents on most Philippine highways and roads, then accidents may be prevented.  Many traffic incidents that occur these days include trucks, buses, and motorcyclists. Even when they are not in the official motorcycle lanes, most motorbikes would overtake as often as possible to escape heavy traffic because these vehicles tend to travel through even the steepest parts of the road. This situation may result in a collision between a motorcycle and a high-wheeled vehicle.This study employed the descriptive developmental method of research using the questionnaire in gathering the respondents’ assessment on the road safety services of a transport safety provider.